HUBUNGAN PENGETAHUAN DAN MOTIVASI BELAJAR DENGAN PENERAPAN K3 PADA PRAKTEK PENGOLAHAN MAKANAN KONTINENTAL SISWA SMKN DLANGGU - M. Najamuddin Al Ayyubi; Sri Handajani; Any Sutiadiningsih; Hidayatun Muyasyaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of Occupational Safety and Health (OSH) is important in culinary practice because vocational high school students are exposed to potential workplace accidents during practical activities. This study aimed to analyze the effect of knowledge and learning motivation on the implementation of OSH in Continental Food Practice among students of SMKN 1 Dlanggu. The study employed a quantitative approach with an explanatory research design. The sample consisted of 33 eleventh-grade culinary students selected using the total sampling technique. Data were collected through a knowledge test, a learning motivation questionnaire, and an observation sheet on OSH implementation. Data were analyzed using multiple linear regression with SPSS version 25. The results showed that knowledge had a significant effect on OSH implementation (Sig. = 0.026), while learning motivation had no significant effect (Sig. = 0.061). Simultaneously, knowledge and learning motivation had no significant effect on OSH implementation (Sig. = 0.072). The research variables explained 16.1% of the variance in OSH implementation.